Crustal deformation of the Andean foreland at 31° 30′S (Argentina) constrained by magnetotelluric survey - Orozco, Luz Amparo (2013)
Twenty-five new long-period magnetotelluric sites near 31.5°S were collected in a west–east profile. This profile and the previous one, aligned with and adjacent to the eastern end, have been merged to form a single profile of more than 700 km long, extending from the Precordillera to the Chaco-Pampean Plain. The geotectonic scenario is characterized by a modern flat subduction zone of the Nazca plate located at a depth of around 120 km and clearly defined by the distribution of earthquake hypocenters recorded by local and regional networks. A “bulge” shape at 68.5°W, with an anomalous dip to the west, is observed within this segment. The smooth slab deformation might result from the restriction on eastward motion due to the presence of an electrically resistive zone. The magnetotelluric model shows that this thick zone of increased resistivity is found from shallow crustal levels to upper mantle depths. The bulge geometry allows hot fluids and volatiles to rise from the deeper asthenospheric wedge, and reach the lower crust reducing its viscosity and letting it flow. The zones of low resistivity in the lower crust show spatial correlation with the areas of foreland deformation from Precordillera to the Sierras Pampeanas and may also suggest a ductile regime. Shear zones reactivated by Cenozoic faulting must necessarily have their roots in the levels of the ductile lower crust associated to conductive channels. The zone where the lower crust is closer to the surface coincides with the areas of greatest structural relief and erosion. The interface between the folded ductile lower crust and the brittle upper crust might act as the main level of décollement of the bordering structures between the Precordillera, Sierra de Pie de Palo and the Sierras Pampeanas. In addition, the geometry of the interface might be conditioning the vergence of those structures.